A case report of tigecycline induced acute pancreatitis in a renal transplant patient and review of the literature: Should we avoid tigecycline in patients on calcineurin inhibitors?. Issue 4 (11th March 2021) - Yazirli, Bercemhan; Kara, Emre; Inkaya, Ahmet Cagkan; Maden, Sarpcan; Ozberk, Ugur; Yildirim, Tolga; Parlak, Erkan; Uzun, Omrum; Yilmaz, Seref Rahmi; Arici, Mustafa
Abstract: Tigecycline has been approved by the US (United States) Food and Drug Administration in a variety of complicated infections due to its broad‐spectrum antibiotic activity. Following phase III trials, the product label was revised and acute pancreatitis was listed as an adverse effect. Its safety profile in special groups such as renal transplant patients is not exactly known. We report the first case of unintentional rechallenge of tigecycline induced pancreatitis in a renal transplant patient. Ten days following the renal transplantation, a 35‐year‐old patient presented to the clinic with acute rejection. He received anti‐thymocyte globulin (ATG) and pulse steroid treatments for rejection. Following the treatment, he developed perianal cellulitis and tigecycline was started. Nine days following initiation of tigecycline he received thrombectomy for his incidental cardiac thrombus. One day after thrombectomy, he developed acute pancreatitis (AP). Thrombectomy was suspected to be the cause of AP. During hospitalization for transplant rejection, tigecycline was re‐started for a newly developed complicated abdominal infection. On the third day of the tigecycline re‐treatment, he developed a second episode of AP. Following tigecycline withdrawal, his symptoms resolved and serum pancreatic enzymes returned to normal, thus AP was ultimately attributed to tigecycline. This lethal side effect should be kept in mind while treating severe infections in renal transplant recipients.